CAPITAL AND REVENUE PROFITS AND LOSSES. - Thompson, R. R. (The Accounting Review, 1932)
Abstract The article presents information about capital and revenue profits and losses. A profit is an increase in value. It may result through the sale of an asset, in which case the asset is replaced by cash, or an obligation to pay cash, of a greater value. A profit may also arise through an increase in the value of an asset itself, when viewed from a certain standpoint. The asset is not sold, but is simply regarded as being more valuable. In this case it is an unrealized profit, not being represented by cash in any way. There is one asset which obviously must be excepted from this rule, and that is cash itself. If a concern has cash abroad, a change in a rate of exchange can make a very real and immediate profit or loss. Profits and Losses are divided into those of Revenue, and those of Capital. Revenue profits and losses arise out of regular operations of the concern, which will be buying, manufacturing, and selling its products, or simply buying and selling merchandise of some kind. Capital profits and losses arise out of a transaction in a capital asset or liability, and accordingly one outside of the regular operations of the company.